2019
DOI: 10.4111/icu.2019.60.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative and follow-up neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients with non-metastatic clear cell renal cell carcinoma

Abstract: PurposeTo evaluate the significance of preoperative and follow-up neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as prognostic factors for recurrence in patients with non-metastatic clear cell renal cell carcinoma (NMCCRCC).Materials and MethodsWe retrospectively reviewed the medical records of 309 patients with NMCCRCC who underwent radical or partial nephrectomy. The prognostic significance of various clinicopathological variables, preoperative NLR (pNLR) and PLR (pPLR), and NLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…The identification of accurate predictors of clinical outcome is imperative to determine individualized follow-up strategies and to facilitate counseling regarding adjuvant therapy. At present, prediction of tumor relapse for patients with surgically treated localized ccRCC is based on clinical and pathological features, including TNM stage, nuclear grade, which can be subject to inter-observer variability and might not entirely account for individual tumor biology 789. These limitations have led to much research aimed at identifying more accurate molecular markers that lead to better identification and counseling for patients with RCC.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of accurate predictors of clinical outcome is imperative to determine individualized follow-up strategies and to facilitate counseling regarding adjuvant therapy. At present, prediction of tumor relapse for patients with surgically treated localized ccRCC is based on clinical and pathological features, including TNM stage, nuclear grade, which can be subject to inter-observer variability and might not entirely account for individual tumor biology 789. These limitations have led to much research aimed at identifying more accurate molecular markers that lead to better identification and counseling for patients with RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Although some researcher found NLR, PLR and AST/ALT and Alb level could be used as prognostic factors in RCC [8][9][10][11][12], in population of RCC with TT we could not found any statistically signi cant difference. Firstly, we supposed in patients of RCC with TT, the in ammatory status could be more complex, thus these kinds of blood marker may not suitable for speci c kind of populations.…”
Section: Discussionmentioning
confidence: 62%
“…Preoperative In ammation indicators such as neutrophils, lymphocytes, platelets, neutrophil-lymphocyte ratio (NLR) and the platelet lymphocyte ratio (PLR) have been demonstrated to be prognostic value in some urologic malignancies like prostate cancer and bladder cancer [6,7]. In RCC, elevated neutrophils, platelets, NLR, PLR and decreased lymphocytes was associated with worse survival in previous study [8][9][10][11]. Besides, other preoperative blood parameters like hemoglobin, AST/ALT, albumin have been reported as prognostic factors in predicting RCC survival [12].…”
Section: Introductionmentioning
confidence: 97%
“…These subtle differences in cutoff values may be due to differences in timing of tests, differences in disease states, differences in the host's immune response, and differences in tumor characteristics. However, most previous studies also reported the role of the PLR as a poor prognostic factor for survival outcomes in mRCC [21][22][23][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that platelet volume is significantly associated with worse survival outcomes. A different study by Kim et al [ 22 ] that analyzed the data of 309 patients with non-mRCC demonstrated that a higher neutrophil-to-lymphocyte ratio and PLR is associated with shorter recurrence-free survival. More recently, Huszno et al [ 23 ] tried to evaluate the prognostic role of the PLR in patients with mRCC.…”
Section: Discussionmentioning
confidence: 99%